Baby skin care research programme: assessor-blinded randomised controlled trial comparing impregnated cleansing wipes with water in infants. (7th June 2011) - Lavender, T; Furber, C; Cork, M; Campbell, M; Victor, S
Abstract : Background: The use of baby wipes is common for cleansing of babies' skin. However, with the use of wipes come differing, and often conflicting perceptions, due to an absence of published research tackling the safety and efficacy of disposable baby wipes. Although studies have evaluated the use of baby wipes, these have tended to be on older babies or those in the neonatal unit. Hypothesis: The use of an optimally formulated cleansing wipe on the napkin area of newborns (<1 month) has an equivalent effect on skin hydration when compared with using cotton wool and water (usual care). Method: An investigator led randomised, assessor-blinded clinical trial was conducted to compare a fragrance free cleansing wipe with water for cleansing the napkin area. Healthy term newborns (n=280), from the NW England were randomised to either cleansing with a baby wipe or with water only. Babies were stratified according to family history of atopic eczema. The primary outcome measure was change in hydration from within 48 h of birth to 4 weeks post birth. Secondary outcomes include trans-epidermal water loss and skin pH. We used standard statistical techniques to analyse the data, taking into account treatment group and the stratification variable. Key findings: At 4 weeks, hydration scores, pH and trans-epidermal water loss were equivalent in both groups. Implications for practice: There are currently inconsistencies in advice given to women. This study will enable informed decision making and optimise maternal choice in cleansing newborns.